ANALISIS KELAYAKAN FINANSIAL USAHATANI SELADA (Lactuca sativa L.) DENGAN SISTEM HIDROPONIK NFT (Nutrient Film Technique) - Adi Widiyanto (Fakultas Pertanian UVAYA Banjarmasin, 2019)
Aim of this research was to know: (1) Financial feasibility of lettuce farming on hydroponic system at Surgi Mufti sub-district, North Banjarmasin District, Banjarmasin city, (2) Payback Periode for lettuce farming on hydroponic system. The research conducted on April 2019. Type of the research was a case study research at lettuce farmer Surgi Mufti sub-district. Sample was taken by purposive sampling on lettuce farmer that make an effort on hydroponic system actively. Result of this research showed that lettuce farming with hydropinic system NFT (Nutrient Film Tecnique) w as f ea si bl e w it h NPV value Rp. 3.851.058,- Net B/C 1,52, Gross B/C 1,13, IRR 26,31%. Payback periode (PP) from investment that has been spent from lettuce farming with hydroponic system NFT (Nutrient Film Technique) was 2 years 11 months and 15days